Passion trumps instruction - Abd Razak, Dzulkifli (2010)
THE news to boost creativity and innovation in schools cannot come at a better time; after all this is the Year of Creativity and Innovation. Indeed, learning is all about creating and innovating, rather than memorising and regurgitating as we are accustomed to. Admittedly, however, the latter is easier, which is the reason it has been the mainstay for a long time.